LANGUAGE STYLES IN ZOOTOPIA 2: A SOCIOLINGUISTIC ANALYSIS OF CHARACTER INTERACTION AND SOCIAL REPRESENTATION - M. Rismawan; Badri (LPPM Universitas Bina Bangsa, 2026)
This research explores language styles in Zootopia 2 as a representation of social interaction and identity formation in cinematic discourse. Film dialogue serves not just as a means of communication but also mirrors social relationships, power structures, and cultural values. The study aims to identify the various language styles used, analyze their roles in character interactions, and examine how they reflect social realities. It adopts a qualitative descriptive methodology within a sociolinguistic framework. The data include selected dialogues from main and supporting characters, gathered through observation and transcription. Using Martin Joos’ classification, the analysis reveals all five styles are present, with casual style being most prevalent, indicating natural and close interpersonal communication. Formal and consultative styles occur in institutional settings, while the intimate style appears in emotionally charged interactions. The findings suggest that language styles in Zootopia 2 are essential for shaping character identity, guiding interactions, and portraying broader social issues within the storyline.